Different impacts of parental psychological and behavioral control on the cultivation of advantageous strength in Chinese rural adolescent - Wang, Rong; Liu, Min; Sun, Yinghong; Li, Qian (Frontiers in Psychology, 2024)
Numerous studies have focused on the mental and behavioral problems or negative emotions of adolescents when examining the impact of parental control. However, limited research has explored the relationship between parental control and adolescents’ future planning, neglecting the distinctions between parental psychological and behavioral control, as well as the significant roles of personal growth initiative and meaning in life. To investigate the differential effects of parental psychological control and behavioral control on the future planning of rural adolescents in China, a sample of 909 individuals (13.60 ± 0.93 years old, 470 boys and 439 girls) completed a self-report questionnaire anonymously. The study utilized the Adolescent Future Orientation Questionnaire, Parental Control Questionnaire, Adolescents’ Personal Growth Initiative Scale, and Meaning in Life Questionnaire. The findings revealed that parental control significantly influenced the future planning of Chinese rural adolescents, with psychological control and behavioral control exerting distinct impacts in this process. Specifically, parental psychological control was found to have a direct negative effect on adolescents' future planning, while also exhibiting a positive influence due to the masking effect of meaning in life; it did not negatively affect adolescents’ future planning through their personal growth initiative. On the other hand, parental behavioral control was observed to directly and positively impact adolescents’ future planning, as well as positively influence it through the mediating role of personal growth initiative and the chain mediating role of personal growth initiative and meaning in life. These results suggest that the influence of parental control on adolescents’ future planning is not a simple, singular mechanism, but rather a multi-layered and complex process, yielding mixed outcomes as a result of psychological control, behavioral control, and other factors. This complexity should be taken into consideration in educational practices and future research endeavors.